Pethitan: Understanding the End Tone System in Javanese Gamelan | Pethitan: Pemahaman Sistem Nada Ujung Pada Gamelan Jawa - Ardana I Ketut; Rizky Muhamad Yunus; Anom Suneko (GHURNITA: Jurnal Seni Karawitan, 2021)
Pethitan is a new composition inspired by the system of tones found in Javanese gamelan. One of them is the end of each ricikan. This end tone is called pethit.  Verbally this term is often referred to by tweeters, teachers, and researchers. However, in the notes of various documents, scientific writings, there is no comprehensive description of pethit. Hence, it is necessary to reactivate the concept through artwork research, then this artwork is titled Pethitan. The purpose of creating Pethitan's karawitan composition work is to realize the work of karawitan composition by exploring the concept of pethit. The method of art creation is an empirical method consisting of observation, discography, and literature studies. In addition, it also uses methods of building works and presentation of works. The pethit tones in this composition are explored from three different Javanese gamelan devices of basic tones. Therefore, each end tone of each device has a different frequency. This difference is a source to realize musical elements in melodies, rhythms, and composition dynamics.